IDENTIFIKASI PENGGUNAAN ALAT EVALUASI PADA MATA DIKLAT AKUNTANSI KELAS XI DI SMKN 4 SURABAYA - JOKO MAHADMA (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study purposive to determine the evaluation tools for teacher in SMKN 4 Surabaya. And reasons teacher choose the learning evaluation tools, determine the feasibility of evaluation tools, and study the attitude and response of student to the evaluation tools used. This study is a descriptive research with quantitative approach. The results showed that the evaluation tools used in SMKN 4 Surabaya is test, the type is written test in narrative form. from the review or evaluation tools expert obtained the result that evaluation tools narrative form used in SMKN 4 Surabaya has categorized decent. The result of students attitude and responses to the evaluation tools they use are good. Keywords: Evaluation Tool, accounting, vocational school